1997
DOI: 10.1143/jjap.36.6595
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Grown-in Defects during Czochralski Silicon Crystal Growth

Abstract: The formation behavior of grown-in defects in Czochralski silicon (CZ-Si) crystals was investigated using two crystals that were quenched during growth but in one case after crystal growth had been halted for 5 h. The distributions of grown-in defect density and size, and their micro-structures were analyzed as a function of temperature during crystal growth just before quenching by means of an optical precipitate profiler (OPP) and an atomic force microscope (AFM) coupled with a laser particle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 11 publications
0
29
0
2
Order By: Relevance
“…The final metric is the so-called nucleation temperature, which is the temperature at which visible voids are suddenly formed during crystal growth. Many experiments [12][13][14]41,42] have shown that the measurable void size distribution suddenly begins to evolve once a crystal segment has cooled to about 1100 1C and then evolves for a short time until all mobile species have been incorporated into stable clusters. There is wide consensus that the nucleation and growth temperature interval, which somewhat depends on the cooling conditions during growth, is in the range 1050-1110 1C.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The final metric is the so-called nucleation temperature, which is the temperature at which visible voids are suddenly formed during crystal growth. Many experiments [12][13][14]41,42] have shown that the measurable void size distribution suddenly begins to evolve once a crystal segment has cooled to about 1100 1C and then evolves for a short time until all mobile species have been incorporated into stable clusters. There is wide consensus that the nucleation and growth temperature interval, which somewhat depends on the cooling conditions during growth, is in the range 1050-1110 1C.…”
Section: Resultsmentioning
confidence: 99%
“…In this case the void densities were probed by measuring the GOI of test capacitor structures grown over the entire wafer surface [13,14]. Note that the number of capacitor failures (gate-oxide breakdowns) due to the presence of one or more voids is now related to the surface void density.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Formation of the microvoids is occurs in two stages [35]. In the first stage in the temperature range 1403...1343 K occurs rapidly growth of sizes.…”
Section: Osf-ringmentioning
confidence: 99%
“…Recent efforts especially in wafer cleaning, and etching technology have markedly reduced the density of particles or contaminants on silicon wafer surfaces. However, there is another type of "particle" commonly found by the laser particle counter on the Czochralski-grown single crystal silicon wafer surface, which is typically called crystal originated "particles" (COPs) [1], [2]. COPs have been Manuscript recognized as surface defects or micropits, which originate from grown-in defects [3].…”
Section: Introductionmentioning
confidence: 99%